ANALISIS PELAFALAN MELALUI MEDIA DUBBING PADA MAHASISWA PENDIDIKAN BAHASA MANDARIN ANGKATAN 2021 FKIP UNTAN - Louis, Louis; Afrimonika, Yoanna; Khiong, Bun Yan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This research aims to investigate pronunciation issues faced by students when learning Mandarin and to evaluate and understand the impact of the video dubbing media learning method on pronunciation. Through recording and testing methods, the author found that most students experience pronunciation problems and a lack of confidence when embodying characters in videos. This is particularly evident in mispronouncing the second tone as the fourth tone and the first tone as the third tone, with students struggling to express the emotions conveyed by characters in the videos. Additionally, there are issues with the pronunciation of initial consonants. Through a questionnaire survey, the author also discovered that the majority of students believe that the video dubbing media learning method can help them practice Mandarin better, remember Mandarin characters, improve pronunciation standards, make learning more interesting, and boost their confidence. In conclusion, students consider the video dubbing media learning method as an engaging and effective tool in enhancing their Mandarin pronunciation and daily language usage skills.